Vascular contribution to cognitive impairment and dementia (VCID): proceedings of 2025 workshop of the Jackson Laboratory - Mehwish Anwer; Tetiana Poliakova; Ricardo D’Oliveira Albanus; Mohammad Iqbal H. Bhuiyan; Adam M. Brickman; Soumilee Chaudhuri; Leah Cuddy; Maxwell Eisenbaum; Kate Foley; Douglas B. Gould; Catherine Hall; Costantino Iadecola; et al. (Mammalian Genome, 2026)
The first Vascular Contributions to Cognitive Impairment and Dementia (VCID) Workshop, held on May12-16, 2025 at The Jackson Laboratory, provided scientific content and career development training in the latest developments in VCID and Alzheimer’s Disease (AD) and related dementia (ADRD). The Workshop aimed to foster interdisciplinary collaborations and empower the next generation of diverse scientists to advance ADRD research from mechanism to intervention. The meeting placed a strong emphasis on neurovascular pathology, its central role in ADRD pathogenesis, its modulation by both central and peripheral factors, and the critical need to dissect the mechanistic basis of VCID through experimental models. The workshop included talks from both faculty and trainees and was bookended by two keynote addresses by Drs. Donna Wilcock and Costantino Iadecola, leaders and pioneers in the VCID field. The second VCID workshop is planned for April 28-May 1, 2026, to be held at Washington University in St. Louis.

Prioritizing chemicals for developmental neurotoxicity by integrating data from a new approach methods (NAMs) battery covering key cellular events in neurodevelopment - Laura A. Hall; Jui-Hua Hsieh; Skylar W. Marvel; Mamta Behl; Ellen Fritsche; Katharina Koch; Anna Kreutz; Marcel Leist; Arantza Muriana; Timothy J. Shafer; Jason P. Stanko; Robert C. Sills; et al. (NeuroToxicology, 2026)

Carbon source and weather in coastal North Carolina - Christopher L. Osburn; Thomas S. Bianchi; Hans W. Paerl; Nathan S. Hall; Alexandria G. Hounshell; Jacob C. Rudolph; Ruchi Bhattacharya; Ryan W. Paerl (Limnology and Oceanography, 2026)
The increasing frequency of extreme weather events, including tropical cyclones, is altering the delivery and quality of organic matter (OM) exported from landscapes to estuaries. However, the mechanisms regulating these shifts, especially during multi‐year climatic oscillations, remain poorly understood. We used a new fluorescence–based mixing model to estimate dissolved OM (DOM) sources to the Neuse River Estuary, during a dry period (2010–2012) and a wet period (2015–2019), both punctuated by extreme precipitation events. Wet periods were characterized by positive anomalies in dissolved organic carbon (DOC) and a 350 —a proxy for colored DOM (CDOM)—relative to dry period median values. During the wet period, extreme rainfall events collapsed the longitudinal gradient of wetland‐derived DOC between the tidal freshwater reach and the estuary mouth, resulting in spatial homogenization of source contributions. These events coincided with DOC and a 350 values that significantly exceeded dry‐year medians, indicating hydrologically driven expansion of land–ocean connectivity and downstream replacement of background river–ocean mixtures of DOM with wetland‐derived carbon. We propose the Carbon Source and Weather (C‐SAW) paradigm, in which wetter conditions poise coastal watersheds to release pulses of DOM stored in the coastal landscape following extreme rainfall. These events overwhelm long‐residence time estuaries with distinctive DOM from wetland soils, sediments, and water, and potentially lead to dramatic changes to the estuarine carbon cycle. C‐SAW integrates elements of the Flood Pulse and Pulse‐Shunt Concepts, providing a unifying framework linking watershed carbon storage, hydrologic connectivity, and estuarine carbon cycling.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

96-h methamphetamine self-administration elicits striatal dopamine depletion in male and female rats: a model of binge-like use - Bo Jarrett Wood; Ethan D. Brackett; Nicole M. Hall; Christopher E. Cannon; Robert D. Dayton; Courtney M. Keller; Nicholas E. Goeders; Kevin S. Murnane (Psychopharmacology, 2026)
Background Methamphetamine is a psychostimulant with significant public health implications. Chronic methamphetamine use is linked to profound dysregulation of the dopaminergic system, cognitive deficits, and psychiatric symptoms. While traditional experimenter administered “binge” dosing models reliably produce dopaminergic neurotoxicity, they fail to capture the volitional, drug intake characteristic of human methamphetamine use. Although self-administration paradigms better reflect human drug-taking behavior, they have yet to consistently reproduce the neurochemical deficits seen in the non-contingent models. Methods In this study, we employed a very long-access (96-h) methamphetamine self-administration model over eight weeks to evaluate whether contingent, volitional drug intake produces dopaminergic neurotoxicity. Male and female rats were given extended access to methamphetamine (0.06 mg/kg/infusion) for 96-h sessions weekly, with saline-yoked controls. Neurochemical analysis focused on striatal dopamine and metabolites to assess drug-induced alterations. Results Rats exhibited significant escalation in methamphetamine intake over eight weeks, with no sex differences in total intake. Importantly, striatal dopamine levels were significantly reduced in both male and female methamphetamine self-administering rats compared to saline-yoked controls, representing the first demonstration of dopamine depletion following voluntary administration methamphetamine self-administration. Dopamine depletion was significantly correlated with total methamphetamine intake. Interestingly, no significant changes were observed in dopamine metabolites (DOPAC, HVA). Conclusions These findings demonstrate that volitional methamphetamine intake under a 96-h access model induces robust dopaminergic deficits, paralleling those seen in non-contingent binge dosing. This model provides a translationally relevant paradigm, capturing both the behavioral and neurobiological aspects of human methamphetamine use, supporting its utility for investigating neurotoxicity and potential treatments.

Exploring the Potential Probiotic Properties of Bifidobacterium breve DSM 32583—A Novel Strain Isolated from Human Milk - Magdalena Kujawska; Klaus Neuhaus; Christopher Huptas; Esther Jiménez; Silvia Arboleya; Monika Schaubeck; Lindsay J. Hall (Probiotics and Antimicrobial Proteins, 2025)

Population-level phylogenomic analysis yields insights into species cohesion and population substructure of Lobelia section Lobelia (Campanulaceae) - Grant T. Godden; Andrew A. Crowl; Stephen R. Patten; Princess Abu; Svea Hall; Mark O. Johnston; Douglas W. Schemske; T. Wayne Barger; Miguel A. Pérez-Pérez; Christopher R. Herlihy; Lynda F. Delph; Christopher B. Blackwood; et al. (Molecular Phylogenetics and Evolution, 2025)

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Experimental Immigration Mediates Ecological Selection and Drift in Monarch Microbiome Assembly - Christopher P. Catano; James G. DuBose; Lydia Fuller‐Hall; Joselyne Chavez; Jacobus C. de Roode (Ecology Letters, 2025)
The distribution of biodiversity depends on processes operating across scales, yet multiscale paradigms have struggled to permeate host‐microbiome research. Instead, host‐microbiome research has focused on host selection and has struggled to explain the high variation in microbial composition across individuals. By integrating multi‐scale ecological theory with experimental manipulation of bacteria colonizing monarch butterfly caterpillars, we test the hypothesis that immigration from the regional species pool alters the importance of niche selection and drift in causing variation in gut bacterial communities across individuals and through ontogeny. Higher immigration increased the dominance of certain bacteria, causing greater convergence in bacterial composition across the caterpillar life stage. Conversely, limited immigration made colonization more stochastic, resulting in more unpredictable variability in bacterial composition across individuals. Our study reveals that immigration mediates the balance between host selection and drift, demonstrating that processes operating at scales beyond the individual are underappreciated but critical for structuring host‐microbiome symbioses.

Swine production intensity and swine-specific fecal contamination of household surfaces at residences of industrial livestock operation workers and community residents, North Carolina, USA - Kathleen M. Kurowski; Nora Pisanic; Kristoffer Spicer; Kate Kruczynski; Carolyn Gigot; Devon J. Hall; Devon J. Hall; Kyle T. Aune; Bonita Salmerón; Ana M. Rule; Christopher D. Heaney (Science of The Total Environment, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Mortality in a cohort of WTC-exposed law-enforcement officers compared to non-WTC law-enforcement officers - Ankura Singh; Malak Khalifeh; John Violanti; Rachel Zeig-Owens; Andrew C. Todd; Moshe Z. Shapiro; Madeline E. Carwile; Christopher R. Dasaro; Jiehui Li; Janette Yung; Mark R. Farfel; Robert M. Brackbill; et al. (International Archives of Occupational and Environmental Health, 2025)
Purpose World Trade Center (WTC) rescue/recovery workers were exposed to materials hazardous to health. Previous studies found lower than expected mortality among WTC rescue/recovery workers when compared to general populations, possibly due to healthy worker effects, better healthcare access and/or incomparability of the groups. We compared mortality rates in WTC-exposed law enforcement officers (LEOs) with rates in LEOs employed by the Buffalo, NY, Police Department. We also compared both cohorts to the general population. Methods Follow-up began at the later of one year after enrollment date or 1/1/2005 and ended at the earlier of death date or 12/31/2018. Analyses were restricted to ages 40–79 years (N = 11,476 WTC LEOs, N = 1668 non-WTC LEOs). We estimated standardized mortality ratios (SMRs) in each cohort using stratum-specific US mortality rates. Relative rates (RRs) and 95% CIs were estimated for the WTC vs. the Buffalo cohort using Poisson regression models adjusted for sex, race, age-group, and calendar-period. Results 185 deaths were observed in the WTC cohort and 186 in the Buffalo cohort. All-cause and cause-specific SMRs were significantly lower in the WTC cohort. Similarly, the adjusted all-cause mortality RR for the WTC vs. Buffalo cohorts was 0.30 (95% CI = 0.23–0.40). The cause-specific mortality RRs were all significantly < 1. Conclusion We found lower overall and cause-specific mortality rates in WTC LEOs compared with both the general population and Buffalo LEOs. These results suggest that factors other than healthy worker effects, such as access to healthcare via the WTC Health Program, contribute to lower mortality rates in WTC rescue/recovery workers.

How to close the loop with citizen scientists to advance meaningful science - Damon M. Hall; Pedro M. Avellaneda-Lopez; Darren L. Ficklin; Jason H. Knouft; Christopher Lowry (Sustainability Science, 2024)
Citizen science yields increased scientific capacity in exchange for science literacy and promises of a more responsive science to society’s needs. Yet, citizen science projects are criticized for producing few scientific outputs and having exploitative relationships with the citizens who participate. In the eagerness to capture new data, scientists can fail to see the value of citizen scientists’ expertise beyond data generation and can forget to close the loop with outputs that benefit the public interest. Citizen scientists are experts in their local environments who, when asked, can improve scientific processes and products. To the degree that citizen scientists are relegated to data collection, we shortchange opportunities to advance science. Rather than merely critique, we present an evidence-based engagement approach for listening to citizen scientist participants and incorporating their input into science processes and products that can be retrofitted onto existing citizen science projects or integrated from a project’s inception. We offer this adaptable blueprint in four steps and illustrate this approach via a crowdsourced hydrology project on the Boyne River, USA. We show how engaging voices of citizen scientists at key points in the project improves both the products of science (a real-time ecohydrological model) and the process of conducting the science (adaptations to help improve data collection). Distinct from outreach or education, considering citizen scientists as an equally interesting site of inquiry can improve the practice and outputs of science.

Shifts in macroalgae composition alters carbon flow in Coastal Baltic Sea ecosystems: implications for dissolved organic carbon bioavailability and flux - Jack R. Hall; Kristjan Herkül; Federico Baltar; Christopher D. Hepburn; Georg Martin (Frontiers in Marine Science, 2024)
The extracellular release of dissolved organic carbon (DOC) from marine macroalgae supports coastal ecosystem function by supplying photosynthetically fixed carbon to higher trophic levels via the microbial loop. Despite its widely acknowledged biogeochemical importance, DOC is not typically included in primary production estimates of coastal systems. Additionally, little is known about how changes in species composition and coverage will affect the supply of DOC to coastal systems. Within the context of the Baltic Sea, anthropogenic forces are driving a decline in habitat forming kelp species ( Fucus vesiculosus ) which is superseded by filamentous/turfing algal species, a pattern of change observed globally in numerous other aquatic systems. To evaluate how the drivers of this change may impact the flow of carbon within the Baltic Sea coastal system, the production of DOC by the filamentous algae ( Ectocarpus siliculosus ) was examined and its rate of release determined (0.095 mg C · g DW −1 · h −1 in light and 0.070 mg C · g DW −1 · h −1 in dark). In addition, bioassays were used to assess the short-term DOC use by bacteria as a proxy of the lability of the released products, with the majority (28.7% released in light and 18.6% released in dark) of the products remaining after 120 hours. This data was linked with long term macroalgae biomass and coverage surveys in order to assess changes in macroalgae community structure through time and to produce standing stock estimates of F. vesiculosus. DOC production as a metric of algal coverage was used to make a preliminary estimation of how changes in community structure may impact the flow of carbon within the system. Our results suggest that decreased levels of DOC released by filamentous algae relative to F. vesiculosus will act to reduce microbial activity. Our model estimates the presence of approximately 150,000 tonnes of F. vesiculosus (dry weight) within the Estonian coastal system translating to an annual release of 7,391 tonnes of DOC. Our study indicates that filamentous-dominated systems have likely altered carbon flow, impacting the broader ecology of the Baltic Sea. Consequently, the loss of kelp species and the expansion of filamentous algae may alter carbon dynamics, with important ecological consequences for other coastal systems globally.

Reduced seagrass resilience due to environmental and anthropogenic effects may lead to future die-off events in Florida Bay - Jimmy de Fouw; Christopher J. Madden; Bradley T. Furman; Margaret O. Hall; Yvon Verstijnen; Sander Holthuijsen; Thomas A. Frankovich; Theresa Strazisar; Michelle Blaha; Tjisse Van Der Heide (Frontiers in Marine Science, 2024)
Coastal systems often depend on foundation species such as seagrasses that are supported by self-facilitation. Seagrass meadows, however, are threatened worldwide due to climate change and local human impact, disrupting self-facilitation leading to system instability. Florida Bay is a large seagrass dominated coastal ecosystem that suffered from multiple seagrass mortality events over the last half century driven by hypoxia, high water temperatures, hypersalinity, and high biological oxygen demand. These conditions reduce the amount of photosynthetically-derived oxygen in the plant causing sulphide intrusion into meristematic tissues. Using a bay-wide sampling design and long-term monitoring trends of seagrass condition, we investigated the current state of the meadows, sediment characteristics (e.g., organic matter, sulphide, nutrients) and discuss how climate stressors interact with plant and sediment oxygen dynamics. Our survey revealed that at sites where seagrass had been previously denuded by die-off, the dominant seagrass Thalassia testudinum had not recovered, while the pioneering seagrass Halodule wrightii recolonized the impacted areas. Organic matter and sulphide levels were higher at the impacted sites, apparently a persistent characteristic of the formerly dense T. testudinum meadows in central and western Florida Bay. These sediment conditions promote sulphide intrusion of T. testudinum belowground tissue under anoxic conditions. Plant oxidation initially buffers sulphide intrusion, but disruption of this oxidation mechanism due to changing environmental conditions results in widespread mortality and seagrass community collapse. Climate change cannot be fully mitigated by local management, however, attempts can be made to control critical salinity and oxygen levels by increasing freshwater input, reducing hypersalinity and aiming to keep the internal seagrass oxidation feedback intact. Our study shows that the Florida Bay seagrass ecosystem is still recovering four years post die-off and continues to be susceptible to future climate change and system degradation.

Broad-scale pesticide screening finds anticoagulant rodenticide and legacy pesticides in Australian frogs - Jodi J.L. Rowley; Andrew Symons; Christopher Doyle; Jane Hall; Karrie Rose; Laura Stapp; Damian C. Lettoof (Science of The Total Environment, 2024)

The influence of soil organic matter content and substance lipophilicity on the toxicity of pesticides to the earthworm Eisenia andrei - Bart G. van Hall; Christopher J. Sweeney; Melanie Bottoms; Cornelis A.M. van Gestel (Science of The Total Environment, 2024)

Woody Plant–Soil Relationships in Interstitial Spaces Have Implications for Future Forests Within and Beyond Urban Areas - Gisselle A. Mejía; Peter M. Groffman; Meghan L. Avolio; Anika R. Bratt; Jeannine Cavender-Bares; Noortje H. Grijseels; Sharon J. Hall; James Heffernan; Sarah E. Hobbie; Susannah B. Lerman; Jennifer L. Morse; Desiree L. Narango; et al. (Ecosystems, 2024)

Persistent organic pollutants and trace elements detected in New Zealand fur seals (long-nosed fur seal; Arctocephalus forsteri) from New South Wales, Australia, between 1998 and 2019 - Jane Hall; Susan Bengtson Nash; Anil Gautam; Hannah Bender; Benjamin J. Pitcher; Hamish McCallum; Christopher Doyle (Science of The Total Environment, 2023)

Survey of epiphytic microalgae to evaluate risk of ciguatera fish poisoning across natural and artificial reefs in North Carolina - Prisca Lim; Avery B. Paxton; J. Christopher Taylor; Nathan S. Hall (Frontiers in Marine Science, 2023)
Epiphytic microalgae are important contributors to the carbon and nutrient cycles yet are often overlooked during ecological surveys. In reef habitats, epiphytes are often found living on host organisms, including seaweeds or corals, and can influence community composition of higher trophic level taxa. Hence, understanding how epiphytes respond to different reef substrate materials can help inform designs of substrates intentionally deployed to form artificial reefs which can encourage high biodiversity and ecological functioning. One such epiphyte, Gambierdiscus spp., is a harmful benthic dinoflagellate which produces toxins that bioaccumulate and cause ciguatera fish poisoning (CFP) when contaminated fish is consumed by humans. CFP is one of the most frequently reported seafood-associated illnesses around the world, occurring most often near tropical reefs. We surveyed the epiphytes amongst 13 natural and artificial reef sites located off the coast of North Carolina to determine the role of the reefs’ foundational substrate (e.g., natural marl, steel or concrete) on structuring the epiphyte community with an emphasis on Gambierdiscus spp. abundance. No Gambierdiscus spp. were detected among the sampled reefs, likely due to suboptimal water temperatures. An ex-situ substrate preference experiment for Gambierdiscus spp. was performed using marl to represent natural rocky reefs, and steel and concrete to represent artificial reefs. Experimental results indicated that Gambierdiscus spp. grew fastest in the presence of marl and density decreased significantly when exposed to steel. However, steel artificial reefs had the highest average epiphyte biomass and species richness amongst the sampled reefs. 18s rRNA gene sequence analysis revealed that natural reefs were more likely to be dominated by dinoflagellates, whereas steel and concrete reefs were dominated by diatoms. We found that epiphyte composition was related to material at a phylum level, but seaweed hosts played a more significant role at the species level. These findings suggest that CFP risk is relatively low on the reefs studied but natural reefs would likely be preferentially colonized by Gambierdiscus spp. should ambient conditions become appropriate.

Can we predict visitor movement? Using step selection function analysis to map high probability camping areas in a remote Alaskan wilderness - Susan A. Sidder; Ashley D'Antonio; Troy E. Hall; Jonathan B. Dinkins; Evan M. Bredeweg; Christopher A. Monz (Landscape and Urban Planning, 2023)

Environmental optima for common diatoms from Ontario lakes along gradients of lakewater pH, total phosphorus concentration, and depth - Matthew P. Duda; Branaavan Sivarajah; Kathleen M. Rühland; Andrew M. Paterson; Jennifer L. Barrow; Yuanyu Cheng; Elizabeth J. Favot; Kristopher R. Hadley; Roland I. Hall; Kathryn E. Hargan; Clare Nelligan; Euan D. Reavie; et al. (Journal of Paleolimnology, 2023)

Comparison study of ductile iron produced with Martian regolith harvested iron from ionic liquids and Bosch byproduct carbon for in-situ resource utilization versus commercially available 65-45-12 ductile iron - Blake C. Stewart; Haley R. Doude; Shiraz Mujahid; Morgan B. Abney; Eric T. Fox; Jennifer E. Edmunson; Jeffrey J. Mehan; Christopher R. Henry; Phillip B. Hall; Haitham El Kadiri; Hongjoo Rhee (Advances in Space Research, 2023)

A 15-year follow-up study of mortality in a pooled cohort of World Trade Center rescue and recovery workers - Jiehui Li; Charles B. Hall; Janette Yung; Rebecca D. Kehm; Rachel Zeig-Owens; Ankura Singh; James E. Cone; Robert M. Brackbill; Mark R. Farfel; Baozhen Qiao; Maria J. Schymura; Moshe Z. Shapiro; et al. (Environmental Research, 2023)

Temperature mapping of non-photochemical quenching in Chlorella vulgaris - Andrei Herdean; Christopher Hall; David J. Hughes; Unnikrishnan Kuzhiumparambil; Bernardo Campos Diocaretz; Peter J. Ralph (Photosynthesis Research, 2023)
Light intensity and temperature independently impact all parts of the photosynthetic machinery in plants and algae. Yet to date, the vast majority of pulse amplitude modulated (PAM) chlorophyll a fluorescence measurements have been performed at well-defined light intensities, but rarely at well-defined temperatures. In this work, we show that PAM measurements performed at various temperatures produce vastly different results in the chlorophyte Chlorella vulgaris . Using a recently developed Phenoplate technique to map quantum yield of Photosystem II (Y(II)) and non-photochemical quenching (NPQ) as a function of temperature, we show that the fast-relaxing NPQ follows an inverse normal distribution with respect to temperature and appears insensitive to previous temperature acclimation. The slow-relaxing or residual NPQ after 5 minutes of dark recovery follows a normal distribution similar to Y(II) but with a peak in the higher temperature range. Surprisingly, higher slow- and fast-relaxing NPQ values were observed in high-light relative to low-light acclimated cultures. Y(II) values peaked at the adaptation temperature regardless of temperature or light acclimation. Our novel findings show the complete temperature working spectrum of Y(II) and how excess energy quenching is managed across a wide range of temperatures in the model microalgal species C. vulgaris . Finally, we draw attention to the fact that the effect of the temperature component in PAM measurements has been wildly underestimated, and results from experiments at room temperature can be misleading.

The production of dissolved organic carbon by macroalgae and its consumption by marine bacteria: Implications for coastal ecosystems - Jack R. Hall; Gerli Albert; Isla M. Twigg; Federico Baltar; Christopher D. Hepburn; Georg Martin (Frontiers in Marine Science, 2022)
Through the fixation of large quantities of dissolved inorganic carbon (DIC), macroalgae facilitate the energetic foundation of highly productive coastal ecosystems. While the processes controlling photosynthesis and carbon fixation by macroalgae are well known, the fate of organic matter fixed by macroalgae is less well understood. This study quantified release rates of DOC by three ecologically significant Baltic macroalgae species: the perennial habitat forming Fucus vesiculosus and Furcellaria lumbricalis , and the seasonal fast-growing Ulva intestinalis , under both light and dark conditions. The released products were assessed using bacterial incubations whereby radiolabeled leucine was used to evaluate the uptake and lability of these products by marine heterotrophic bacteria. DOC was found to be released by both F. vesiculosus and U . intestinalis at rates of 0.27 mg C·h −1 under light and 0.13 mg C·h −1 per unit of dry mass under dark treatments, respectively, whereas F. lumbricalis DOC release was observed to be negligible under both light and dark. Our findings further validate previous hypotheses that factors such as photosynthetic activity are a primary driver behind DOC release and that DOC release is not an entirely passive process. Additionally, we reaffirm the need to relate a given species life characteristics and habitat in order to understand why DOC products are released. The consumption of macroalgae-derived DOC by heterotrophic bacteria reveals that released DOC is variable in its lability. After a period of 12 h and under maximum photosynthetic conditions, the release of DOC by F. vesiculosus and U . intestinalis achieved a peak rate of 219 µg C·L −1 ·day −1 and 214 µg C·L −1 ·day −1 for each gram of dry weight material, respectively, directly into the microbial loop via heterotrophic bacterial consumption. In contrast, F. lumbricalis ’ low rate of DOC release and the subsequent low bacterial consumption indicate that habitats dominated by this species have a reduced importance in the transfer energy via the microbial loop. These findings have implications for how we view carbon transfer within coastal food webs and highlight how changes in species composition and coverage may dramatically affect coastal ecosystem productivity through the microbial loop.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A National-Level Assessment of Lemur Hunting Pressure in Madagascar - Cortni Borgerson; Steig E. Johnson; Emma Hall; Kerry A. Brown; Pamela R. Narváez-Torres; Be Jean Rodolph Rasolofoniaina; Be Noel Razafindrapaoly; Samuel D. Merson; Katharine E. T. Thompson; Sheila M. Holmes; Edward E. Louis; Christopher D. Golden (International Journal of Primatology, 2022)

Riverine Discharge and Phytoplankton Biomass Control Dissolved and Particulate Organic Matter Dynamics over Spatial and Temporal Scales in the Neuse River Estuary, North Carolina - Alexandria G. Hounshell; Stephen R. Fegley; Nathan S. Hall; Christopher L. Osburn; Hans W. Paerl (Estuaries and Coasts, 2022)

Warming increased bark beetle‐induced tree mortality by 30% during an extreme drought in California - Zachary J. Robbins; Chonggang Xu; Brian H. Aukema; Polly C. Buotte; Rutuja Chitra‐Tarak; Christopher J. Fettig; Michael L. Goulden; Devin W. Goodsman; Alexander D. Hall; Charles D. Koven; Lara M. Kueppers; Gavin D. Madakumbura; et al. (Global Change Biology, 2022)
Quantifying the responses of forest disturbances to climate warming is critical to our understanding of carbon cycles and energy balances of the Earth system. The impact of warming on bark beetle outbreaks is complex as multiple drivers of these events may respond differently to warming. Using a novel model of bark beetle biology and host tree interactions, we assessed how contemporary warming affected western pine beetle ( Dendroctonus brevicomis ) populations and mortality of its host, ponderosa pine ( Pinus ponderosa ), during an extreme drought in the Sierra Nevada, California, United States. When compared with the field data, our model captured the western pine beetle flight timing and rates of ponderosa pine mortality observed during the drought. In assessing the influence of temperature on western pine beetles, we found that contemporary warming increased the development rate of the western pine beetle and decreased the overwinter mortality rate of western pine beetle larvae leading to increased population growth during periods of lowered tree defense. We attribute a 29.9% (95% CI: 29.4%–30.2%) increase in ponderosa pine mortality during drought directly to increases in western pine beetle voltinism (i.e., associated with increased development rates of western pine beetle) and, to a much lesser extent, reductions in overwintering mortality. These findings, along with other studies, suggest each degree (°C) increase in temperature may have increased the number of ponderosa pine killed by upwards of 35%–40% °C −1 if the effects of compromised tree defenses (15%–20%) and increased western pine beetle populations (20%) are additive. Due to the warming ability to considerably increase mortality through the mechanism of bark beetle populations, models need to consider climate's influence on both host tree stress and the bark beetle population dynamics when determining future levels of tree mortality.

Understanding coralline algal responses to ocean acidification: Meta‐analysis and synthesis - Christopher E. Cornwall; Ben P. Harvey; Steeve Comeau; Daniel L. Cornwall; Jason M. Hall‐Spencer; Viviana Peña; Shigeki Wada; Lucia Porzio (Global Change Biology, 2022)
Ocean acidification (OA) is a major threat to the persistence of biogenic reefs throughout the world's ocean. Coralline algae are comprised of high magnesium calcite and have long been considered one of the most susceptible taxa to the negative impacts of OA. We summarize these impacts and explore the causes of variability in coralline algal responses using a review/qualitative assessment of all relevant literature, meta‐analysis, quantitative assessment of critical responses, and a discussion of physiological mechanisms and directions for future research. We find that most coralline algae experienced reduced abundance, calcification rates, recruitment rates, and declines in pH within the site of calcification in laboratory experiments simulating OA or at naturally elevated CO 2 sites. There were no other consistent physiological responses of coralline algae to simulated OA (e.g., photo‐physiology, mineralogy, and survival). Calcification/growth was the most frequently measured parameters in coralline algal OA research, and our meta‐analyses revealed greater declines in seawater pH were associated with significant decreases in calcification in adults and similar but nonsignificant trends for juveniles. Adults from the family Mesophyllumaceae also tended to be more robust to OA, though there was insufficient data to test similar trends for juveniles. OA was the dominant driver in the majority of laboratory experiments where other local or global drivers were assessed. The interaction between OA and any other single driver was often additive, though factors that changed pH at the surface of coralline algae (light, water motion, epiphytes) acted antagonistically or synergistically with OA more than any other drivers. With advances in experimental design and methodological techniques, we now understand that the physiology of coralline algal calcification largely dictates their responses to OA. However, significant challenges still remain, including improving the geographic and life‐history spread of research effort and a need for holistic assessments of physiology.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Influence of neighbourhoods on the extent and compactness of tropical tree crowns and root systems - Christopher Madsen; Matthias Kunz; Goddert von Oheimb; Jefferson Hall; Katherine Sinacore; Benjamin L. Turner; Catherine Potvin (Trees, 2021)

Differential household vulnerability to climatic and non-climatic stressors in semi-arid areas of Mali, West Africa - Alcade C. Segnon; Edmond Totin; Robert B. Zougmoré; Jourdain C. Lokossou; Mary Thompson-Hall; Benjamin O. Ofori; Enoch G. Achigan-Dako; Christopher Gordon (Climate and Development, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Impact of Extreme Disturbances on Suspended Sediment in Western Florida Bay: Implications for Seagrass Resilience - Jonathan R. Rodemann; W. Ryan James; Rolando O. Santos; Bradley T. Furman; Zachary W. Fratto; Valentina Bautista; Jan Lara Hernandez; Natasha M. Viadero; Joshua O. Linenfelser; Lulu A. Lacy; Margaret O. Hall; Christopher R. Kelble; et al. (Frontiers in Marine Science, 2021)
Seagrasses are threatened worldwide due to anthropogenic and natural disturbances disrupting the multiple feedbacks needed to maintain these ecosystems. If the disturbance is severe enough, seagrass systems may undergo a regime shift to a degraded system state that is resistant to recovery. In Florida Bay, Florida, United States, two recent, large-scale disturbances (a drought-induced seagrass die-off in 2015 and Hurricane Irma in 2017) have caused 8,777 ha of seagrass beds to degrade into a turbid, unvegetated state, causing a large sediment plume. Using satellite imagery digitization and long-term seagrass cover data, we investigate the expansion of this sediment plume between 2008 and 2020 and the potential interaction of this sediment plume with seagrass recovery in two focal basins in Florida Bay affected by the die-off, Johnson and Rankin. The average size of the sediment plume increased by 37% due to the die-off and Hurricane Irma, increasing from an average of 163.5 km 2 before the disturbances to an average of 223.5 km 2 . The expansion of the plume was basin-specific, expanding into Johnson after the 2015 seagrass die-off with expansive and long-lasting effects, but only expanding into Rankin after Hurricane Irma with less severe and short-term effects. Furthermore, the sediment plume was negatively correlated with seagrass cover in Johnson, but held no relationship with seagrass cover in Rankin. Thus, different disturbances can act upon seagrass ecosystems at varying scales with varying consequences. This study illustrates the advantage of combining satellite imagery with field data to monitor disturbances as well as highlights the importance of investigating disturbances of seagrass ecosystems at various scales to comprehend seagrass resilience in the context of future extreme events.

Association between cytoreductive nephrectomy and survival among patients with metastatic renal cell carcinoma receiving modern therapies: a systematic review and meta-analysis examining effect modification according to systemic therapy approach - Mary E. Hall; Bimal Bhindi; Amy N. Luckenbaugh; Aaron A. Laviana; Kelvin A. Moses; Raj Satkunasivam; Brian Rini; Zachary Klaassen; Christopher J. D. Wallis (Cancer Causes & Control, 2021)

A Decade of Incorporating Social Sciences in the Integrated Marine Biosphere Research Project (IMBeR): Much Done, Much to Do? - Ingrid van Putten; Rachel Kelly; Rachel D. Cavanagh; Eugene J. Murphy; Annette Breckwoldt; Stephanie Brodie; Christopher Cvitanovic; Mark Dickey-Collas; Lisa Maddison; Jess Melbourne-Thomas; Haritz Arrizabalaga; Kumiko Azetsu-Scott; et al. (Frontiers in Marine Science, 2021)
Successful management and mitigation of marine challenges depends on cooperation and knowledge sharing which often occurs across culturally diverse geographic regions. Global ocean science collaboration is therefore essential for developing global solutions. Building effective global research networks that can enable collaboration also need to ensure inter- and transdisciplinary research approaches to tackle complex marine socio-ecological challenges. To understand the contribution of interdisciplinary global research networks to solving these complex challenges, we use the Integrated Marine Biosphere Research (IMBeR) project as a case study. We investigated the diversity and characteristics of 1,827 scientists from 11 global regions who were attendees at different IMBeR global science engagement opportunities since 2009. We also determined the role of social science engagement in natural science based regional programmes (using key informants) and identified the potential for enhanced collaboration in the future. Event attendees were predominantly from western Europe, North America, and East Asia. But overall, in the global network, there was growing participation by females, students and early career researchers, and social scientists, thus assisting in moving toward interdisciplinarity in IMBeR research. The mainly natural science oriented regional programmes showed mixed success in engaging and collaborating with social scientists. This was mostly attributed to the largely natural science (i.e., biological, physical) goals and agendas of the programmes, and the lack of institutional support and push to initiate connections with social science. Recognising that social science research may not be relevant to all the aims and activities of all regional programmes, all researchers however, recognised the (potential) benefits of interdisciplinarity, which included broadening scientists’ understanding and perspectives, developing connections and interlinkages, and making science more useful. Pathways to achieve progress in regional programmes fell into four groups: specific funding, events to come together, within-programme-reflections, and social science champions. Future research programmes should have a strategic plan to be truly interdisciplinary, engaging natural and social sciences, as well as aiding early career professionals to actively engage in such programmes.

Neuropsychological Assessment and Screening in Heart Failure: a Meta-Analysis and Systematic Review - Eric J. Connors; Alexander O. Hauson; Brianna D. Barlet; Sharis Sarkissians; Nicholas P. Stelmach; Alyssa D. Walker; Natasha M. Nemanim; Kristina L. Greenwood; Nicholas J. Chesher; Scott C. Wollman; Kenneth E. Allen; Matthew G. Hall; et al. (Neuropsychology Review, 2021)

Minding the Data-Gap Trap: Exploring Dynamics of Abundant Dolphin Populations Under Uncertainty - Erin Ashe; Rob Williams; Christopher Clark; Christine Erbe; Leah R. Gerber; Ailsa J. Hall; Philip S. Hammond; Robert C. Lacy; Randall Reeves; Nicole L. Vollmer (Frontiers in Marine Science, 2021)
Preventing declines in common species is key to sustaining the structure and function of marine ecosystems. Yet for many common marine mammals, including oceanic dolphins, statistical power to detect declines remains low due to patchy distribution and large variability in group sizes. In this study, population viability analyses (PVA) were used to model the dynamics of four oceanic dolphin populations off the United States West Coast: eastern North Pacific long-beaked common dolphins ( Delphinus delphis capensis ), short-beaked common dolphins ( D. delphis delphis ), Pacific white-sided dolphins ( Lagenorhynchus obliquidens ), and “offshore” common bottlenose dolphins ( Tursiops truncatus ). We calibrated the PVA with life-history tables, studies on proxy species, and stock assessment reports. We explored the sensitivity of populations to demographic variation and projected how they may respond to changes in three sublethal threats (prey limitation, ocean noise, and chemical pollution) and one lethal threat (fisheries bycatch). We found the most serious projected declines in long-beaked common dolphins, which showed the lowest birth rate. Most threat scenarios resulted in declines that would not be detected by existing monitoring programs in the United States, which are among the most data-rich surveys of their kind. The cumulative effects of the three sublethal stressors exceeded the effect of the one lethal stressor (fisheries bycatch). To implement pro-active management and monitoring programs, anticipating which cetaceans are more at risk and which anthropogenic threats could cause declines is paramount. Our study highlights the value of model testing with PVA when monitoring data are poor, thereby identifying priorities for future research, monitoring, and management.

Lung abnormalities do not influence aerobic capacity in school children born preterm - Christopher A. O’Dea; Karla Logie; Andrew C. Wilson; J. Jane Pillow; Conor Murray; Georgia Banton; Shannon J. Simpson; Graham L. Hall; Andrew Maiorana (European Journal of Applied Physiology, 2021)

Spontaneous Capillary Imbibition of Water and Nonaqueous Liquids into Dry Quarry Limestones - Christopher Hall; Victoria Pugsley (Transport in Porous Media, 2020)
Rates of spontaneous imbibition of water and nonaqueous liquids into dry limestones have been measured at 25 °C. Thirteen English and French limestones were used, with eight liquids (water, decane, dodecane, sec-butanol, iso-propanol, tetrahydrofuran, perfluorodimethylcyclohexane, ethanediol). For the nonaqueous liquids, the measured sorptivity generally scales as (surface-tension/viscosity) $$^{1/2}$$ 1 / 2 (here called F -scaling). Water sorptivities deviate from F -scaling, indicating partial wetting. A wetting coefficient (wetting index) is derived. Data show that there is little difference in the Hirschwald saturation coefficient measured with the different liquids, although there is a large variation between stones. Results suggest that physicochemical alteration of exposed pore surfaces strongly (and unpredictably) influences the capillary absorption of water by limestones.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Disinfection options for irrigation water: Reducing the risk of fresh produce contamination with human pathogens - Catherine E. Dandie; Abiodun D. Ogunniyi; Sergio Ferro; Barbara Hall; Barbara Drigo; Christopher W. K. Chow; Henrietta Venter; Baden Myers; Permal Deo; Erica Donner; Enzo Lombi (Critical Reviews in Environmental Science and Technology, 2020)

Revealing hydrogen peroxide as an external stressor in macrophyte-dominated coastal ecosystems - Isla M. Twigg; Federico Baltar; Jack R. Hall; Christopher D. Hepburn (Oecologia, 2020)

Liver Transcriptome Profiling Reveals That Dietary DHA and EPA Levels Influence Suites of Genes Involved in Metabolism, Redox Homeostasis, and Immune Function in Atlantic Salmon (Salmo salar) - Xi Xue; Jennifer R. Hall; Albert Caballero-Solares; Khalil Eslamloo; Richard G. Taylor; Christopher C. Parrish; Matthew L. Rise (Marine Biotechnology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Snow and Climate: Feedbacks, Drivers, and Indices of Change - Chad W. Thackeray; Chris Derksen; Christopher G. Fletcher; Alex Hall (Current Climate Change Reports, 2019)

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

Cancer-associated mucins: role in immune modulation and metastasis - Rakesh Bhatia; Shailendra K. Gautam; Andrew Cannon; Christopher Thompson; Bradley R. Hall; Abhijit Aithal; Kasturi Banerjee; Maneesh Jain; Joyce C. Solheim; Sushil Kumar; Surinder K. Batra (Cancer and Metastasis Reviews, 2019)

Rising Sea Levels: Helping Decision-Makers Confront the Inevitable - John A. Hall; Christopher P. Weaver; Jayantha Obeysekera; Mark Crowell; Radley M. Horton; Robert E. Kopp; John Marburger; Douglas C. Marcy; Adam Parris; William V. Sweet; William C. Veatch; Kathleen D. White (Coastal Management, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

Growth, Photosynthesis, and Cold Tolerance of Eucalyptus benthamii Planted in the Piedmont of North Carolina - John R Butnor; Kurt H Johnsen; Peter H Anderson; Kevin B Hall; Joshua M Halman; Gary J Hawley; Christopher A Maier; Paul G Schaberg (Forest Science, 2019)

Natural acidification changes the timing and rate of succession, alters community structure, and increases homogeneity in marine biofouling communities - Norah E. M. Brown; Marco Milazzo; Samuel P. S. Rastrick; Jason M. Hall‐Spencer; Thomas W. Therriault; Christopher D. G. Harley (Global Change Biology, 2018)
Ocean acidification may have far‐reaching consequences for marine community and ecosystem dynamics, but its full impacts remain poorly understood due to the difficulty of manipulating p CO 2 at the ecosystem level to mimic realistic fluctuations that occur on a number of different timescales. It is especially unclear how quickly communities at various stages of development respond to intermediate‐scale p CO 2 change and, if high p CO 2 is relieved mid‐succession, whether past acidification effects persist, are reversed by alleviation of p CO 2 stress, or are worsened by departures from prior high p CO 2 conditions to which organisms had acclimatized. Here, we used reciprocal transplant experiments along a shallow water volcanic p CO 2 gradient to assess the importance of the timing and duration of high p CO 2 exposure (i.e., discrete events at different stages of successional development vs. continuous exposure) on patterns of colonization and succession in a benthic fouling community. We show that succession at the acidified site was initially delayed (less community change by 8 weeks) but then caught up over the next 4 weeks. These changes in succession led to homogenization of communities maintained in or transplanted to acidified conditions, and altered community structure in ways that reflected both short‐ and longer‐term acidification history. These community shifts are likely a result of interspecific variability in response to increased p CO 2 and changes in species interactions. High p CO 2 altered biofilm development, allowing serpulids to do best at the acidified site by the end of the experiment, although early (pretransplant) negative effects of p CO 2 on recruitment of these worms were still detectable. The ascidians Diplosoma sp. and Botryllus sp. settled later and were more tolerant to acidification. Overall, transient and persistent acidification‐driven changes in the biofouling community, via both past and more recent exposure, could have important implications for ecosystem function and food web dynamics.

Effects of nalfurafine on the reinforcing, thermal antinociceptive, and respiratory-depressant effects of oxycodone: modeling an abuse-deterrent opioid analgesic in rats - E. Andrew Townsend; Jennifer E. Naylor; S. Stevens Negus; Shelley R. Edwards; Hina N. Qureshi; Hunter W. McLendon; Christopher R. McCurdy; Coco N. Kapanda; Jussara M. do Carmo; Fernanda S. da Silva; John E. Hall; Kenneth J. Sufka; et al. (Psychopharmacology, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Clinical Phenotype of Adult Fragile X Gray Zone Allele Carriers: a Case Series - Sarah M. Debrey; Maureen A. Leehey; Olga Klepitskaya; Christopher M. Filley; Raj C. Shah; Benzi Kluger; Elizabeth Berry-Kravis; Elaine Spector; Flora Tassone; Deborah A. Hall (The Cerebellum, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

A framework for understanding climate change impacts on coral reef social–ecological systems - Joshua Eli Cinner; Morgan Stuart Pratchett; Nicholas Anthony James Graham; Vanessa Messmer; Mariana Menezes Prata Bezerra Fuentes; Tracy Ainsworth; Natalie Ban; Line Kolind Bay; Jessica Blythe; Delphine Dissard; Simon Dunn; Louisa Evans; et al. (Regional Environmental Change, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Analysis of Integrin Alpha2Beta1 (α2β1) Expression as a Biomarker of Skeletal Metastasis - Christopher L. Hall; Evan T. Keller (Exposure and Health, 2016)

Sustainable development education, practice, and research: an indigenous model of sustainable development at the College of Menominee Nation, Keshena, WI, USA - Michael J. Dockry; Katherine Hall; William Van Lopik; Christopher M. Caldwell (Sustainability Science, 2016)

Rare taxa have potential to make metabolic contributions in enhanced biological phosphorus removal ecosystems - Christopher E. Lawson; Blake J. Strachan; Niels W. Hanson; Aria S. Hahn; Eric R. Hall; Barry Rabinowitz; Donald S. Mavinic; William D. Ramey; Steven J. Hallam (Environmental Microbiology, 2015)
Summary Enhanced biological phosphorus removal ( EBPR ) relies on diverse but specialized microbial communities to mediate the cycling and ultimate removal of phosphorus from municipal wastewaters. However, little is known about microbial activity and dynamics in relation to process fluctuations in EBPR ecosystems. Here, we monitored temporal changes in microbial community structure and potential activity across each bioreactor zone in a pilot‐scale EBPR treatment plant by examining the ratio of small subunit ribosomal RNA ( SSU r RNA ) to SSU r RNA gene (r DNA ) over a 120 day study period. Although the majority of operational taxonomic units ( OTUs ) in the EBPR ecosystem were rare, many maintained high potential activities based on SSU r RNA : r DNA ratios, suggesting that rare OTUs contribute substantially to protein synthesis potential in EBPR ecosystems. Few significant differences in OTU abundance and activity were observed between bioreactor redox zones, although differences in temporal activity were observed among phylogenetically cohesive OTUs . Moreover, observed temporal activity patterns could not be explained by measured process parameters, suggesting that other ecological drivers, such as grazing or viral lysis, modulated community interactions. Taken together, these results point towards complex interactions selected for within the EBPR ecosystem and highlight a previously unrecognized functional potential among low abundance microorganisms in engineered ecosystems.

Macroalgal responses to ocean acidification depend on nutrient and light levels - Paula S. M. Celis-PlÃ¡; Jason M. Hall-Spencer; Paulo Antunes Horta; Marco Milazzo; Nathalie Korbee; Christopher E. Cornwall; FÃ©lix L. Figueroa (Frontiers in Marine Science, 2015)

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Ocean acidification through the lens of ecological theory - Brian Gaylord; Kristy J. Kroeker; Jennifer M. Sunday; Kathryn M. Anderson; James P. Barry; Norah E. Brown; Sean D Connell; Sam Dupont; Katharina E. Fabricius; Jason M. Hall-Spencer; Terrie Klinger; Marco Milazzo; et al. (Ecology, 2015)
Ocean acidification, chemical changes to the carbonate system of seawater, is emerging as a key environmental challenge accompanying global warming and other human‐induced perturbations. Considerable research seeks to define the scope and character of potential outcomes from this phenomenon, but a crucial impediment persists. Ecological theory, despite its power and utility, has been only peripherally applied to the problem. Here we sketch in broad strokes several areas where fundamental principles of ecology have the capacity to generate insight into ocean acidification's consequences. We focus on conceptual models that, when considered in the context of acidification, yield explicit predictions regarding a spectrum of population‐ and community‐level effects, from narrowing of species ranges and shifts in patterns of demographic connectivity, to modified consumer–resource relationships, to ascendance of weedy taxa and loss of species diversity. Although our coverage represents only a small fraction of the breadth of possible insights achievable from the application of theory, our hope is that this initial foray will spur expanded efforts to blend experiments with theoretical approaches. The result promises to be a deeper and more nuanced understanding of ocean acidification and the ecological changes it portends.

Intraspecific priority effects and disease interact to alter population growth - Christopher J. Dibble; Spencer R. Hall; Volker H. W. Rudolf (Ecology, 2014)
Intraspecific variation may shape colonization of new habitat patches through a variety of mechanisms. In particular, trait variation among colonizing individuals can produce intraspecific priority effects (IPEs), where early arrivers of a single species affect the establishment or growth of later conspecifics. While we have some evidence for the importance of IPEs, we lack a general understanding of factors affecting their presence or magnitude across a landscape. Specifically, IPEs should depend strongly on success of colonizers in the new habitat patch. This success hinges on interactions between colonizer traits and local selective pressures, but such context dependence remains unexplored experimentally. We addressed this gap by looking for the dynamical signature of IPEs in environments with and without a selective (parasite) pressure. We tested whether IPEs affected the population dynamics of a zooplankton host species ( Daphnia dentifera ) collected from two populations showing a tradeoff between growth rate and resistance to a fungal parasite ( Metschnikowia bicuspidata ). Differences in arrival order significantly altered population growth during a period of rapid resource depletion, driving large (up to 65%) differences in population abundance. Furthermore, the presence of IPEs was context dependent, as parasites reduced the impact of early arrivers on later arrivers. Such context‐dependent IPEs, mediated by colonizer traits, colonization order, and selective pressures, may play an unanticipated role in the ecological and evolutionary dynamics of natural metapopulations. This mechanism highlights the overall importance of intraspecific variation for understanding ecological patterns.

Mitochondrial metabolism, reactive oxygen species, and macrophage function-fishing for insights - Christopher J. Hall; Leslie E. Sanderson; Kathryn E. Crosier; Philip S. Crosier (Journal of Molecular Medicine, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Differential trends in mercury concentrations in double-crested cormorant populations of the Canadian Prairies - Britt D. Hall; Jennifer L. Doucette; Lara M. Bates; Aleksandra Bugajski; Som Niyogi; Christopher M. Somers (Ecotoxicology, 2014)

Trait-mediated indirect effects, predators, and disease: test of a size-based model - Christopher R. Bertram; Mark Pinkowski; Spencer R. Hall; Meghan A. Duffy; Carla E. Cáceres (Oecologia, 2013)

Transfer of auxinic herbicide resistance from Brassica kaber to Brassica juncea and Brassica rapa through embryo rescue - J. Mithila; J. Christopher Hall (In Vitro Cellular & Developmental Biology - Plant, 2013)

Integrin alpha2beta1 (α2β1) promotes prostate cancer skeletal metastasis - Joseph L. Sottnik; Stephanie Daignault-Newton; Xiaotun Zhang; Colm Morrissey; Maha H. Hussain; Evan T. Keller; Christopher L. Hall (Clinical & Experimental Metastasis, 2013)

Rate of onset of inhibition of gut-wall and hepatic CYP3A by clarithromycin - Sara K. Quinney; Srikar R. Malireddy; Raj Vuppalanchi; Mitchell A. Hamman; Naga Chalasani; J. Christopher Gorski; Stephen D. Hall (European Journal of Clinical Pharmacology, 2013)

A comparative gradient approach as a tool for understanding and managing urban ecosystems - Christopher G. Boone; Elizabeth Cook; Sharon J. Hall; Marcia L. Nation; Nancy B. Grimm; Carol B. Raish; Deborah M. Finch; Abigail M. York (Urban Ecosystems, 2012)

Purification of the therapeutic antibody trastuzumab from genetically modified plants using safflower Protein A-oleosin oilbody technology - Michael D. McLean; Rongji Chen; Deqiang Yu; Kor-Zheng Mah; John Teat; Haifeng Wang; Steve Zaplachinski; Joseph Boothe; J. Christopher Hall (Transgenic Research, 2012)

The spleen contributes to stroke induced neurodegeneration through interferon gamma signaling - Hilary A. Seifert; Christopher C. Leonardo; Aaron A. Hall; Derrick D. Rowe; Lisa A. Collier; Stanley A. Benkovic; Alison E. Willing; Keith R. Pennypacker (Metabolic Brain Disease, 2012)

Infection by Pythium aphanidermatum increases production of phenolics in hydroponically grown peppers and predisposes healthy plants to root rot - T. Nathaniel Owen-Going; Clifford W. Beninger; J. Christopher Hall; John C. Sutton (European Journal of Plant Pathology, 2012)

Deep Bed Filtration Modelling of Formation Damage Due to Particulate Invasion from Drilling Fluids - Edo S. Boek; Christopher Hall; Philippe M. J. Tardy (Transport in Porous Media, 2012)

Cultivable bacteria from ancient algal mats from the McMurdo Dry Valleys, Antarctica - Doug E. Antibus; Laura G. Leff; Brenda L. Hall; Jenny L. Baeseman; Christopher B. Blackwood (Extremophiles, 2012)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

The association between height and prostate cancer grade in the Early Stage Prostate Cancer Cohort Study - Wildon R. Farwell; Christopher Lourenco; Erika Holmberg; Robert B. Hall; Leonard D’Avolio; Elizabeth V. Lawler; J. Michael Gaziano (Cancer Causes & Control, 2011)

Interpreting spatial language in image captions - Mark M. Hall; Philip D. Smart; Christopher B. Jones (Cognitive Processing, 2011)

Ligand-Binding Mass Spectrometry to Study Biotransformation of Fusion Protein Drugs and Guide Immunoassay Development: Strategic Approach and Application to Peptibodies Targeting the Thrombopoietin Receptor - Michael P. Hall; Colin Gegg; Kenneth Walker; Christopher Spahr; Robert Ortiz; Vimal Patel; Steven Yu; Liana Zhang; Hsieng Lu; Binodh DeSilva; Jean W. Lee (The AAPS Journal, 2010)

Administration of a Sigma Receptor Agonist Delays MCAO-Induced Neurodegeneration and White Matter Injury - Christopher C. Leonardo; Aaron A. Hall; Lisa A. Collier; Suzanne M. Green; Alison E. Willing; Keith R. Pennypacker (Translational Stroke Research, 2010)

Immediate fate of angled-and-released Australian bass Macquaria novemaculeata - Christopher E. Dowling; Karina C. Hall; Matt K. Broadhurst (Hydrobiologia, 2010)

Hydrologic control of nitrogen removal, storage, and export in a mountain stream - Robert Jr. O. Hall; Michelle A. Baker; Christopher D. Arp; Benjamin J. Koch (Limnology and Oceanography, 2009)
Nutrient cycling and export in streams and rivers should vary with flow regime, yet most studies of stream nutrient transformation do not include hydrologic variability. We used a stable isotope tracer of nitrogen ( 15 N) to measure nitrate (NO 3 − ) uptake, storage, and export in a mountain stream, Spring Creek, Idaho, U.S.A. We conducted two tracer tests of 2‐week duration during snowmelt and baseflow. Dissolved and particulate forms of 15 N were monitored over three seasons to test the hypothesis that stream N cycling would be dominated by export during floods, and storage during low flow. Floods exported more N than during baseflow conditions; however, snowmelt floods had higher than expected demand for NO 3 − because of hyporheic exchange. residence times of benthic N during both tracer tests were longer than 100 d for ephemeral pools such as benthic algae and wood biofilms. Residence times were much longer in fine detritus, insects, and the particulate N from the hyporheic zone, showing that assimilation and hydrologic storage can be important mechanisms for retaining particulate N. Of the tracer N stored in the stream, the primary form of export was via seston during periods of high flows, produced by summer rainstorms or spring snowmelt the following year. Spring Creek is not necessarily a conduit for nutrients during high flow; hydrologic exchange between the stream and its valley represents an important storage mechanism.

Relationship between urbanization and bat community structure in national parks of the southeastern U.S. - Susan C. Loeb; Christopher J. Post; Steven T. Hall (Urban Ecosystems, 2009)

Modelling the time course of shade, temperature, and wood recovery in streams with riparian forest restoration - Robert J. Davies‐Colley; Mark A. Meleason; Raeme M.J. Hall; J. Christopher Rutherford (New Zealand Journal of Marine and Freshwater Research, 2009)
Action is increasingly being taken in New Zealand and elsewhere to restore ecological function to streams through planting of riparian zones. We used simulation modelling to explore the relative performance of three strategies to restore the riparian zone of a pastoral stream to native forest by: (1) passive regeneration; (2) planting then abandonment of a Pinus radiata plantation; and (3) active restoration by planting selected native trees. We linked the forest model LINKNZ with a shade and temperature model (sWAIORA), and a wood model (OSU_STREAMWOOD) to simulate recovery trajectories for key forest stream attributes in hypothetical streams (1.3–14.0 m channel width) in the central North Island, New Zealand. Both active restoration strategies outperformed passive regeneration in shade, temperature and stream wood volume for most of the simulation time (800 years). Although the abandoned pine plantation provided greatest shade initially (

Inhibition of Cryptosporidium parvum infection of a mammalian cell culture by recombinant scFv antibodies - Nicholas J. Pokorny; Jeanine I. Boulter-Bitzer; J. Christopher Hall; Jack T. Trevors; Hung Lee (Antonie van Leeuwenhoek, 2008)

Relative Wulst volume is correlated with orbit orientation and binocular visual field in birds - Andrew N. Iwaniuk; Christopher P. Heesy; Margaret I. Hall; Douglas R. W. Wylie (Journal of Comparative Physiology A, 2008)

The role of Wnts in bone metastases - Christopher L. Hall; Evan T. Keller (Cancer and Metastasis Reviews, 2007)

Degradation of water quality in Lough Neagh, Northern Ireland, by diffuse nitrogen flux from a phosphorus‐rich catchment - Lynda Bunting; Peter R. Leavitt; Christopher E. Gibson; Edward J. McGee; Valerie A. Hall (Limnology and Oceanography, 2007)
Annually resolved fossil records of nitrogen (N) inputs (as sedimentary δ 15 N, N content), aquatic production (δ 13 C, C content), and algal abundance and gross community composition (pigments, nonsiliceous microfossils) from Lough Neagh, Northern Ireland (NI), were compared with annual records of climatic variability, atmospheric and urban nutrient loading, whole‐catchment nutrient budgets, and limnological monitoring data to identify the unique effects of N on the eutrophication of a phosphorus (P)‐rich lake during ca. 1933‐1995. Cluster analysis revealed two major biostratigraphic zones. Zone I (ca. 1933–1955) was characterized by moderate lake production, as inferred from low concentrations of most fossil pigments and reduced δ 15 N signatures but elevated δ 13 C values and chlorophyte microfossil concentrations. In contrast, Zone II (ca. 1955‐1995) exhibited greatly increased contents of 15 N, N, C, and algal pigments, combined with strongly reduced δ 13 C ratios and chlorophyte fossil abundance, a pattern consistent with recent severe eutrophication. Overall, microfossils of diazotrophic cyanobacteria were most abundant during the transition period between zones (ca. 1955‐1964). Regression analysis revealed that past N influx to the lake (as δ 15 N; r 2 = 0.916, p 2 = 0.837, p 2 = 0.388, p 2 δ 15 N = 0.503, p 2 cyanobacteria = 0.296, p 2 total algae = 0.046, p

Invasion in a heterogeneous world: resistance, coexistence or hostile takeover? - Brett A. Melbourne; Howard V. Cornell; Kendi F. Davies; Christopher J. Dugaw; Sarah Elmendorf; Amy L. Freestone; Richard J Hall; Susan Harrison; Alan Hastings; Matt Holland; Marcel Holyoak; John Lambrinos; et al. (Ecology Letters, 2007)
We review and synthesize recent developments in the study of the invasion of communities in heterogeneous environments, considering both the invasibility of the community and impacts to the community. We consider both empirical and theoretical studies. For each of three major kinds of environmental heterogeneity (temporal, spatial and invader‐driven), we find evidence that heterogeneity is critical to the invasibility of the community, the rate of spread, and the impacts on the community following invasion. We propose an environmental heterogeneity hypothesis of invasions, whereby heterogeneity both increases invasion success and reduces the impact to native species in the community, because it promotes invasion and coexistence mechanisms that are not possible in homogeneous environments. This hypothesis could help to explain recent findings that diversity is often increased as a result of biological invasions. It could also explain the scale dependence of the diversity–invasibility relationship. Despite the undoubted importance of heterogeneity to the invasion of communities, it has been studied remarkably little and new research is needed that simultaneously considers invasion, environmental heterogeneity and community characteristics. As a young field, there is an unrivalled opportunity for theoreticians and experimenters to work together to build a tractable theory informed by data.

Efficacy and Mechanisms of α-Solasonine-and α-Solamargine-Induced Cytolysis on Two Strains of Trypanosoma cruzi - Christopher A. Hall; Traci Hobby; Martin Cipollini (Journal of Chemical Ecology, 2006)

Viscoelastic behaviour aids extrusion from and reabsorption of the liquid phase into the digesta plug: creep rheometry of hindgut digesta in the common brushtail possum Trichosurus vulpecula - Roger G. Lentle; Yacine Hemar; Christopher E. Hall (Journal of Comparative Physiology B, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Transgenic Tobacco Plants Expressing a Dimeric Single-chain Variable Fragment (scFv) Antibody Against Salmonella enterica Serotype Paratyphi B - Shokouh Makvandi-Nejad; Michael D. McLean; Tomoko Hirama; Kurt C. Almquist; C. Roger MacKenzie; J. Christopher Hall (Transgenic Research, 2005)

Periodic fluid extrusion and models of digesta mixing in the intestine of a herbivore, the common brushtail possum (Trichosurus vulpecula) - Roger G. Lentle; Yacine Hemar; Christopher E. Hall; Kevin J. Stafford (Journal of Comparative Physiology B, 2005)

Essential role for hematopoietic Fas ligand (FasL) in the suppression of melanoma lung metastasis revealed in bone marrow chimeric mice - Christopher L. Hall; Mike Yao; Laurie L. Hill; Laurie B. Owen-Schaub (Clinical & Experimental Metastasis, 2004)

A Flavanone and Two Phenolic Acids from Chrysanthemum morifolium with Phytotoxic and Insect Growth Regulating Activity - Clifford W. Beninger; Mamdouh M. Abou-Zaid; Adrienne L. E. Kistner; Rebecca H. Hallett; Muhammad J. Iqbal; Bernard Grodzinski; J. Christopher Hall (Journal of Chemical Ecology, 2004)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)